Genetic diversity and structure of native maize races from Northwestern Mexico - Vega-Alvarez, Isrrael; Santacruz-Varela, Amalio; Rocandio-Rodríguez, Mario; Córdova-Téllez, Leobigildo; López-Sánchez, Higinio; Muñoz-Orozco, Abel; Hernández-Bautista, Aurelio (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the genetic diversity of nine maize races (Zea mays ssp. mays) from Northwestern Mexico and one population of teosinte of the Balsas race (Zea mays ssp. parviglumis). A total of 649 alleles were identified, with an average of 20.9 alleles per locus using 31 microsatellite loci; 84.3% of them were polymorphic loci with a 0.49 expected heterozygosity. Graphic representation of principal coordinate analysis (PCoA) showed broad variation and population distribution. The highest probabilistic value obtained with the ΔK criterion confirmed the existence of five population groups clustered by the Bayesian model. This grouping coincided with the population distribution observed in the PCoA graph. Maize races examined retain broad genetic diversity among and within the evaluated populations.